“Come-no-go/l’ennemi…dans la maison”: Reflections on the Lingoes of Conflict in Cameroon’s Urban History - Henry Kam Kah (Modern Africa, 2019)
The re-introduction of multi-party politics and the liberalisation of politics in Cameroon during the 1990s unleashed a venomous language of conflict in some cities. In the coastal region, the expression of “come-no-go,” synonymous to a dreaded skin disease, was/is frequently used to denigrate people from the grassfields of the country. Many were descendants of migrants to the commercial plantations established by the Germans. Meanwhile, the archbishop of Yaounde at the time called Anglophones “l’ennemi dans…la maison” or “enemies in the house.” This followed the launching of the Social Democratic Front (SDF) party in Bamenda against a government ban. This article examines the power of derogatory language in Cameroon’s urban space. Lingoes of conflict and segregation have denigrated some people and remain a challenge to national unity and integration in Cameroon since the reunification of 1961.